International Investment and Firm Performance: Empirical Evidence from Small Open Economies - Ville Kaitila; John McQuinn; Iulia Siedschlag; Xiaoheng Zhang (The Research Institute of the Finnish Economy (ETLA), 2013)
This paper examines the causal link between foreign investment and firm performance in six small open economies in the European Union. Specifically, using micro data for manufacturing and services over the period 2001–2009, we analyse the effects of foreign mergers and acquisitions on labour productivity and employment growth up to five years after acquisition. Our results indicate that foreign investors tend to acquire larger firms in both manufacturing and services. Other characteristics of acquired firms differ across countries and between manufacturing and services. Taken together, our estimates suggest that foreign investment had stronger effects on firm performance in services in comparison to manufacturing.
Keywords: F16; F23; J24; 330; Multinational firms; Productivity; Employment; Propensity score matching; Übernahme; Auslandsinvestition; Arbeitsproduktivität; Erwerbstätigkeit; Industrie; Dienstleistungssektor; EU-Staaten